Questioning morality through absurdity in Hinton’s 'The Outsider' (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
In this study, the writer has two main aims. They are (1) to explain how morality is portrayed in the novel and (2) to explain how morality is questioned through absurdity. This study is a qualitative analysis. The data were collected by reading, identifying, and classifying excerpts from the novel and analyzed by interpreting process of elucidating the binary opposition which later was reversed (the hierarchy) by applying Derrida’s deconstruction theory. After conducting this study, the writer came at two conclusions. First, the morality in The Outsiders was portrayed by appearances and judgments, neglecting various factors such as reasons, conditions, and motives behind particular actions. Second, considering other factors mentioned before, the writer implied that most of those moral-immoral things portrayed in the novel were merely bias. In oversimplified words, morality is an idea comes from one’s perspective (subjective), yet many people thought they could differ the right from the wrong. Thinking those entire possibilities, raised fundamental question, is not morality so absurd? Does morality even exist in the first place?